2016
DOI: 10.1007/s11356-016-6707-0
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-oxidizing archaea and bacteria in water columns and sediments of a highly eutrophic plateau freshwater lake

Abstract: Both ammonia-oxidizing archaea (AOA) and bacteria (AOB) can play important roles in the microbial oxidation of ammonia nitrogen in freshwater lake, but information on spatiotemporal variation in water column and sediment community structure is still limited. Additionally, the drivers of the differences between sediment and water assemblages are still unclear. The present study investigated the variation of AOA and AOB communities in both water columns and sediments of eutrophic freshwater Dianchi Lake. The abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…The nitrogen content of many urban lakes in the middle and lower reaches of the Yangtze River in China is usually high (Chen et al ; Wu et al ; Hou et al ). This high nitrogen concentrations could change the community structure of the AOA and AOB (Yang et al ). However, the existence and diversity of comammox bacteria in these urban lakes, and their relationships with other ammonia‐oxidizing micro‐organisms, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen content of many urban lakes in the middle and lower reaches of the Yangtze River in China is usually high (Chen et al ; Wu et al ; Hou et al ). This high nitrogen concentrations could change the community structure of the AOA and AOB (Yang et al ). However, the existence and diversity of comammox bacteria in these urban lakes, and their relationships with other ammonia‐oxidizing micro‐organisms, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Archaeal and bacterial amoA genes have been frequently used as molecular markers to examine the community structure of ammonia-oxidizing archaea (AOA) and bacteria (AOB) in sediments and soils. [13][14][15][16] Microbially mediated nitrication generally occurs in the presence of oxygen in lake sediments and varies greatly across spatial and temporal scales. 17 Sediment nitrication rates are strongly inuenced by local water quality and sediment properties, including NH 4 + availability and organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms oxidise NH 4 + to NO 2 − by using the ammonia monooxygenase enzyme, the α‐subunit of which is encoded by the amoA gene, a common genetic marker for nitrification (Rotthauwe, Witzel, & Liesack, ). The ecological importance of AOA and AOB communities has been investigated in a variety of freshwater ecosystems, such as rivers (Liu, Huang, Sun, Xu, & Xu, ; Magalhaes, MacHado, & Bordalo, ), lakes (Hou et al., ; Yang et al., ), reservoirs (Hugoni et al., ), and wetlands (Sims et al., ; Wang, Feng, Ma, & Gu, ). In oligotrophic, high‐altitude lakes, studies have shown that planktonic ammonia‐oxidising communities can vary with sampling site and time (Auguet, Nomokonova, Camarero, & Casamayor, ; Hayden & Beman, ; Hu et al., ; Vissers et al., ).…”
Section: Introductionmentioning
confidence: 99%